Corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing and preparation method thereof

By using annealed stainless steel mesh and modified PTFE materials in the tetrafluoro soft tape bushing, combined with high pressure cold spraying and passivation treatment, the corrosion and cost of the tetrafluoro soft tape bushing during use is solved, achieving higher corrosion resistance and mechanical properties.

CN119710671APending Publication Date: 2025-03-28JIANGXI DONGFANG LEOPARD TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411890495.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing tetrafluoro-soft belt bushings are prone to corrosion due to the micro-primary battery effect during use, and the high cost of tin bronze mesh limits its application range.

Method used

A stainless steel mesh is used as a substrate, a chromium-rich oxide film is formed by annealing, and the modified PTFE material is laid on the stainless steel mesh to form a clad structure. The method includes high-pressure cold spraying of zinc-nickel composite powder, annealing treatment, plasticizing process to prepare soft belt bushings, and passivation treatment to improve corrosion resistance.

Benefits of technology

The corrosion resistance and mechanical properties of the tetrafluoro-soft belt bushing are significantly improved, production costs are reduced, the corrosion problem of the original battery is solved, and the salt spray resistance of the bushing is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200537360000051
    Figure BDA0005200537360000051
  • Figure BDA0005200537360000052
    Figure BDA0005200537360000052
  • Figure BDA0005200537360000081
    Figure BDA0005200537360000081
Patent Text Reader

Abstract

The invention provides an anti-corrosion and wear-resistant polytetrafluoroethylene soft belt lining and a preparation method thereof, and belongs to the technical field of automobile parts. The method comprises the following steps: carrying out annealing treatment on a stainless steel mesh of which the surface is cold-sprayed with zinc-nickel composite powder; the modified PTFE material is laid on meshes and the surface of a stainless steel mesh through a plasticizing process, the stainless steel mesh is wrapped in the modified PTFE material, the stainless steel mesh is used as a base material, and the PTFE soft belt wear-resistant material with a mutual wrapping structure is obtained; the material is prepared into the soft belt bushing through an automatic operation process; the soft belt lining with the surface cleaned and subjected to impurity removal is sequentially soaked in a passivation solution, a consolidation solution and a confining solution for passivation treatment, and the corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt lining is obtained after drying. The annealing treatment specifically comprises the following steps: keeping for 1-2 hours at the temperature of 1050-1100 DEG C, cooling to 500 DEG C at the speed of not more than 50 DEG C / h, and then carrying out air cooling or furnace cooling. According to the invention, the stainless steel mesh is used as the lining and is annealed, and the modified PTFE material is used as the outer sleeve, so that the anti-corrosion and wear-resistant characteristics of the lining are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of automobile accessories, and particularly relates to an anti-corrosion and wear-resistant polytetrafluoroethylene soft belt bushing and a preparation method thereof. Background Art

[0002] The PTFE soft belt bushing used for automobile door connection has the advantages of extremely low friction coefficient and chemical resistance, and has been widely used in automobile door connection. Polytetrafluoroethylene (PTFE) has excellent properties such as chemical inertness, high / low temperature resistance and low friction coefficient, and has become one of the main materials for bushings. However, PTFE also has disadvantages such as wear resistance, poor thermal conductivity, hardness, and low strength, which greatly limits its scope of use. In addition, the traditional PTFE soft belt bushing is mainly supported by tin bronze mesh as the internal support, and the surface is coated with polytetrafluoroethylene, which is formed into one piece through a plasticizing process. Since the tin bronze mesh in the PTFE soft belt bushing contains copper, and its matching hinge pin and hinge seat are mainly iron, the two will contact each other after assembly, which will form a micro-galvanic effect, thereby accelerating the corrosion process of the hinge pin and hinge seat mainly composed of iron, and reducing the corrosion resistance of material parts and assemblies. In addition, as a member of the copper material family, the price of tin bronze has remained high, resulting in high material costs. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing and a preparation method thereof, aiming to solve at least one technical problem in the background technology.

[0004] The present invention is achieved in that:

[0005] The first aspect of the present invention provides a method for preparing a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing, comprising the following steps:

[0006] The stainless steel mesh with zinc-nickel composite powder cold-sprayed on the surface is annealed to serve as a substrate;

[0007] The modified PTFE material is laid on the mesh and surface of the stainless steel mesh through a plasticizing process, and the stainless steel mesh is covered therein to make it serve as a skeleton, thereby obtaining a polytetrafluoroethylene soft belt wear-resistant material with a mutually covering structure;

[0008] The soft belt bushing is made of the polytetrafluoroethylene soft belt material through an automated molding process of loading, feeding, unloading, arranging, curling, turning, flanging and shaping;

[0009] The soft belt bushing after cleaning and impurity removal is immersed in passivation liquid, consolidation liquid and sealing liquid in turn for passivation treatment, and after drying, the anti-corrosion and wear-resistant PTFE soft belt bushing is obtained;

[0010] The annealing treatment is specifically: maintaining the temperature at 1050°C-1100°C for 1h-2h, then cooling to 500°C at a rate not exceeding 50°C / h, and then air cooling or furnace cooling.

[0011] Furthermore, the passivation treatment is specifically as follows:

[0012] Clean and remove impurities from the surface of the soft belt bushing, place it in a passivation solution at 70±5℃ for 20 to 40 minutes, and remove the residual passivation solution after cleaning;

[0013] Place in a 60-70°C consolidation solution for 15-20 minutes, and remove the remaining consolidation solution after washing;

[0014] Place in blocking solution for 3-5 minutes and dry.

[0015] Before annealing, the zinc-nickel composite powder is sprayed on the surface of the stainless steel mesh by a high-pressure cold spraying method.

[0016] Furthermore, the modified PTFE material comprises the following components in weight percentage: hydrophobic SiO2 5% to 15%, aluminum silicate powder 5% to 10%, hydroxyl-terminated PDMS 1% to 5%, polyethylene 1% to 3%, carbon fiber 1% to 3%, versatate 1% to 3%, methyltriacetoxysilane 0.5% to 1%; the balance is polytetrafluoroethylene powder.

[0017] Furthermore, the hydroxyl-terminated PDMS has a hydroxyl functional group at the end of the PDMS molecular chain, and is monohydroxyl-terminated or dihydroxyl-terminated.

[0018] Furthermore, the preparation method of the zinc-nickel composite powder comprises:

[0019] The zinc alloy powder is ball-milled into nano-scale powder, and then heat-treated at 600°C to 700°C for 3h to 5h under oxygen flow to obtain Zn-ZuO nano-alloy;

[0020] The Zn-ZuO nano alloy and nickel powder are mixed in proportion and ball-milled to obtain the zinc-nickel composite powder;

[0021] The weight percentage of the Zn-ZuO nano alloy and the nickel powder is: 40% to 70% of the Zn-ZuO nano alloy and 30% to 60% of the nickel powder.

[0022] Furthermore, the oxygen flow rate is 50% to 70% of the theoretical amount.

[0023] Furthermore, in the high-pressure cold spraying method, the pressure is 5MPa-10MPa, the temperature is 500-900°C, and the working gas is nitrogen and / or argon.

[0024] Furthermore, the method for preparing the hydrophobic SiO2 is: mix ethyl orthosilicate and tetrahydrofuran in a molar ratio of 1:5 to 6, add deionized water, add concentrated sulfuric acid until pH = 3 to 4, react at room temperature for 8 to 16 hours, add 3-(methacryloyloxy)propyltrimethoxysilane and stir evenly, let stand to separate the solid and liquid, and obtain hydrophobic SiO2 after drying.

[0025] The second aspect of the present invention provides a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing obtained by the above-mentioned preparation method.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The present invention uses a stainless steel mesh as a substrate, evenly distributes the chromium element on the surface of the stainless steel through annealing, and reacts with oxygen to form a chromium-rich oxide film to cover the surface, further improving the corrosion resistance of the material.

[0028] 2. The present invention uses PTFE material to cover the stainless steel mesh, which enhances the bonding strength between the two and further improves the corrosion resistance of the material.

[0029] 3. The present invention performs annealing treatment on the stainless steel mesh, optimizes the grain structure, evenly distributes metal elements, reduces dimensional changes, and can effectively improve the corrosion resistance of stainless steel.

[0030] 4. The present invention performs incomplete oxidation on the zinc-based alloy to generate metal oxides composed of Zn-ZuO as a dual reinforcement phase, thereby enhancing the toughness and strength of the product.

[0031] 5. The present invention adds hydrophobic SiO2, PDMS terminated with hydroxyl group of aluminum silicate powder, polyethylene, carbon fiber, versatate, and methyltriacetoxysilane to polytetrafluoroethylene, thereby effectively improving the corrosion resistance and mechanical properties.

[0032] 6. The passivation process of the present invention can compensate for the incomplete annealing surface state, making the surface oxide film denser and further improving its corrosion resistance.

[0033] 7. The present invention reduces the production cost by replacing the tin bronze mesh with a stainless steel mesh. The excellent anti-corrosion property of stainless steel improves the salt spray resistance of the soft belt bushing and solves the problem of galvanic corrosion of the assembly from the source. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present invention and are not used to limit the present invention.

[0035] A method for preparing a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing, the method comprising the following steps S1 to S3:

[0036] S1. Spraying zinc-nickel composite powder on the surface of a stainless steel mesh by a high-pressure cold spraying method, and annealing to obtain a stainless steel substrate;

[0037] Among them, in the high-pressure cold spraying method, the pressure is 5MPa~10MPa, the temperature is 500~900℃, and the working gas is nitrogen and / or argon.

[0038] The preparation steps of the zinc-nickel composite powder are as follows: ball-milling the zinc alloy powder into a nano-level powder, and then heat-treating it for 3h to 5h under the condition of oxygen flow and 600°C to 700°C to obtain a Zn-ZuO nano alloy; mixing the Zn-ZuO nano alloy and nickel powder in proportion and ball-milling them to obtain the zinc-nickel composite powder; the weight percentage of the Zn-ZuO nano alloy and the nickel powder is: 40% to 70% of the Zn-ZuO nano alloy and 30% to 60% of the nickel powder;

[0039] During the preparation of zinc-nickel composite powder, the oxygen flow rate is 50% to 70% of the theoretical amount, that is, zinc is not completely oxidized, and the theoretical amount of oxygen flow is set to the amount of oxygen required to fully oxidize Zn and Cu; Zn-ZuO nano alloy contains multiple phases such as ZnO and Zn, among which the metal oxide composed of Zn-ZuO is a dual reinforcement phase, which enhances the toughness and strength of the product.

[0040] In addition, the present invention combines nickel powder with zinc oxide, which has the advantages of strong chemical stability, high hardness, and good acid and alkali corrosion resistance;

[0041] The annealing treatment is as follows: keep the temperature at 1050℃-1100℃ for 1h-2h, then cool to 500℃ at a rate not exceeding 50℃ / h, and then air cool or furnace cool. Annealing of stainless steel mesh can effectively improve the corrosion resistance of stainless steel, including:

[0042] (1) Optimize grain structure: Annealing can reduce internal stress, improve plasticity and toughness, and improve grain structure and corrosion resistance of stainless steel;

[0043] (2) Uniform distribution of metal elements: Through annealing, the metal elements on the surface of stainless steel are evenly distributed. The evenly distributed zinc and nickel elements react with oxygen to form a metal oxide film covering the surface, further improving the corrosion resistance of the product.

[0044] (3) Reduce dimensional changes: Annealing helps reduce the dimensional changes of stainless steel in subsequent use, ensure its dimensional accuracy and stability, thereby avoiding the occurrence of intergranular corrosion and indirectly improving corrosion resistance.

[0045] S2, laying the modified PTFE material on the surface of the stainless steel substrate through a plasticizing process to obtain a soft belt bushing;

[0046] The modified PTFE material comprises the following components in weight percentage: hydrophobic SiO2 5% to 15%, aluminum silicate powder 5% to 10%, hydroxyl-terminated PDMS 1% to 5%, polyethylene 1% to 3%, carbon fiber 1% to 3%, versatate ethylene ester 1% to 3%, methyl triacetoxy silane 0.5% to 1% and the balance is polytetrafluoroethylene powder.

[0047] Because polytetrafluoroethylene (PTFE) powder has low surface energy and small mutual attraction between macromolecules, it has a small friction coefficient. However, after it is prepared into a bushing through processes such as plasticization, the friction coefficient is reduced, and its mechanical properties such as hardness are poor. During use, the product surface is easily damaged by external mechanical forces, resulting in reduced quality and service life.

[0048] The preparation method of hydrophobic SiO2 is as follows: after mixing ethyl orthosilicate and tetrahydrofuran in a molar ratio of 1:5-6, add deionized water, add concentrated sulfuric acid until pH=3-4, react at room temperature for 8-16 hours, add 3-(methacryloyloxy)propyltrimethoxysilane and stir evenly, stand for solid-liquid separation, and dry to obtain hydrophobic SiO2. The role of hydrophobic SiO2 is to increase the hydrophobicity of PTFE materials, increase its surface smoothness, and avoid biological attachment;

[0049] The function of aluminum silicate powder is to improve the hardness and wear resistance of PTFE materials. In addition, aluminum silicate powder is resistant to acid and alkali corrosion. In addition, during the plasticization process, aluminum silicate will interact with the metal interface of the zinc-nickel composite coating to achieve effective metallurgical bonding and in-situ reaction to form a dispersed and uniform Al-based reinforcement phase, thereby improving the mechanical properties of the product.

[0050] The role of hydroxyl-terminated PDMS is to improve the bonding strength of PTFE materials, which is more conducive to its stable bonding with the stainless steel substrate; the molecular structure of PDMS (polydimethylsiloxane) is a linear polymer connected by silicon-oxygen bonds (Si-O), and hydroxyl-terminated PDMS refers to PDMS with hydroxyl (OH) functional groups at the end of the molecular chain. It can be mono-hydroxyl-terminated or di-hydroxyl-terminated, which can be referred to as PDMS-OH;

[0051] The role of carbon fiber is to improve the wear resistance, toughness and strength of PTFE materials;

[0052] Polyethylene, versatate, and methyltriacetoxysilane all play a role in corrosion resistance. Among them, polyethylene has good stability, elongation, water resistance and weather resistance; versatate has good water resistance, UV resistance, heat resistance and alkali resistance, and methyltriacetoxysilane has defoaming and wetting effects, which is conducive to the full dissolution and mutual penetration of the various components of PTFE materials.

[0053] The plasticizing process of the present invention adopts a conventional process flow, including material laying, drying, primary rolling, plasticizing, fine rolling, hemp rolling and other processes, which will not be elaborated in detail here.

[0054] S3, the soft belt bushing after cleaning and impurity removal is immersed in passivation liquid, consolidation liquid and sealing liquid in turn for passivation treatment, and after drying, a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing is obtained;

[0055] Specifically, the surface of the soft belt bushing is cleaned and impurities are removed, and it is placed in a passivation solution at 70±5℃ for passivation for 20-40 minutes, and the residual passivation solution is removed after cleaning; it is placed in a consolidation solution at 60-70℃ for 15-20 minutes, and the residual consolidation solution is removed after cleaning; it is placed in a sealing solution for 3-5 minutes; and then dried.

[0056] Among them, the passivation liquid is 180g / L~210g / L sodium dichromate, 10ml / L-12ml / L sulfuric acid; the consolidation liquid adopts a curing agent permitted in the art to accelerate the curing of PTFE material, such as dihydrogen aluminum phosphate solution; the sealing liquid adopts a sealing agent permitted in the art to reduce direct contact between the bushing and the external environment, such as resin solution.

[0057] The passivation solution, consolidation solution, and sealing solution may be the above-mentioned solutions, but are not limited to the listed solutions. Other solutions with the same functions permitted in the art are also applicable.

[0058] Passivation treatment makes the metal oxide film (NiO X , ZnO) is denser, further improving its corrosion resistance.

[0059] Example 1

[0060] In this embodiment, modified PTFE material and zinc-nickel composite powder are prepared. The modified PTFE material is prepared according to different component ratios, and its components are shown in Table 1; the zinc-nickel composite powder is prepared according to different components and oxygen flow conditions, and its components are shown in Table 2.

[0061] Table 1

[0062]

[0063] Table 2

[0064]

[0065] In Tables 1 and 2, Group E refers to the experimental group, and Group C refers to the control group.

[0066] Example 2

[0067] The influence of different modified PTFE materials on the bushing performance is studied. A method for preparing a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing, the steps are as follows:

[0068] S1. Select 304 stainless steel mesh as the substrate, and use a high-pressure cold spraying method (pressure of 6 MPa, temperature of 600°C, working gas of nitrogen) to spray zinc-nickel composite powder (zinc-nickel composite powder of group E-21 obtained in Example 1) on the surface of the stainless steel mesh to form a zinc-nickel composite coating; then keep the stainless steel mesh at 1080°C for 1.5h, and then cool it at a rate of 50°C / h to 500°C, and then air-cool it to room temperature.

[0069] S2. The annealed stainless steel mesh is paved with the PTFE material obtained in Example 1 (the modified PTFE material of group E-11 obtained in Example 1), including paving, drying, initial rolling, plasticizing, fine rolling, and hemp rolling to prepare a corrosion-resistant and wear-resistant plate. The obtained plate is then placed on an automated soft belt production line to obtain a stainless steel-based polytetrafluoroethylene soft belt bushing.

[0070] S23. Soak the soft belt bushing in a degreasing agent for 4 minutes, then take it out and rinse it with running water, put it in a 70°C passivation solution for 30 minutes, then wash off the passivation solution on the surface of the workpiece with running water, put it in a 70°C consolidation solution for 20 minutes, then wash off the consolidation solution on the surface of the workpiece with running water, put it in a sealing solution for 4 minutes, finally take out the workpiece and dry it.

[0071] Example 3

[0072] The difference between this embodiment and embodiment 2 is that the modified PTFE material adopts the modified PTFE material of group E-12 prepared in embodiment 1, and the other preparation steps are the same as those in embodiment 2.

[0073] Implementation 4

[0074] The difference between this embodiment and embodiment 2 is that the modified PTFE material adopts the modified PTFE material of group E-13 prepared in embodiment 1, and the other preparation steps are the same as those in embodiment 2.

[0075] Example 5

[0076] The difference between this embodiment and embodiment 2 is that the modified PTFE material adopts the modified PTFE material of group E-14 prepared in embodiment 1, and the other preparation steps are the same as those in embodiment 2.

[0077] Example 6

[0078] The difference between this embodiment and embodiment 2 is that the modified PTFE material adopts the modified PTFE material of group E-15 prepared in embodiment 1, and the other preparation steps are the same as those in embodiment 2.

[0079] Comparative Example 1

[0080] The difference between this comparative example and Example 2 is that the modified PTFE material adopts the modified PTFE material of group C-11 prepared in Example 1, and the other preparation steps are the same as those in Example 2.

[0081] Comparative Example 2

[0082] The difference between this comparative example and Example 2 is that the zinc-nickel composite powder adopts the modified PTFE material of group C-12 prepared in Example 1, and the other preparation steps are the same as those in Example 2.

[0083] Comparative Example 3

[0084] The difference between this comparative example and Example 2 is that the modified PTFE material adopts the modified PTFE material of group C-13 prepared in Example 1, and the other preparation steps are the same as those in Example 2.

[0085] Comparative Example 4

[0086] The difference between this comparative example and Example 2 is that the modified PTFE material adopts the modified PTFE material of group C-14 prepared in Example 1, and the other preparation steps are the same as those in Example 2.

[0087] Comparative Example 5

[0088] The difference between this comparative example and Example 2 is that the modified PTFE material adopts the modified PTFE material of group C-15 prepared in Example 1, and the other preparation steps are the same as those in Example 2.

[0089] Comparative Example 6

[0090] The difference between this comparative example and Example 2 is that the modified PTFE material adopts the modified PTFE material of group C-16 prepared in Example 1, and the other preparation steps are the same as those in Example 2.

[0091] Comparative Example 7

[0092] The difference between this comparative example and Example 2 is that the modified PTFE material adopts the modified PTFE material of group C-17 prepared in Example 1, and the other preparation steps are the same as those in Example 2.

[0093] The bushings prepared in Examples 2 to 6 and Comparative Examples 1 to 7 were used as samples to test their friction performance, anti-corrosion performance and hardness.

[0094] Friction performance test method: First, the test sample was ultrasonically cleaned with acetone for 10 minutes, and the tribological properties of the boron nitride / silicon nitride self-lubricating composite material under atmospheric environment at room temperature were studied using a high-temperature friction and wear tester. The friction test conditions were a frequency of 5 Hz, a stroke of 1 mm, a pressure of 0.5 MPa, and the wear partner was a silicon nitride pin. During the test, the friction coefficient was recorded in real time by the data acquisition software.

[0095] The anti-corrosion performance test method adopts salt spray test, including neutral salt spray test (NSS test) and copper salt accelerated acetic acid salt spray test (CASS test). The time when red rust appears is recorded to judge whether it meets the red rust-free aging requirements (neutral salt spray test is 1200h, CASS test is 168h). The results are shown in Table 3.

[0096] Hardness test method: Measure the indentation hardness of the sample in accordance with GB / T 24523-2020 "Metallic Material Rapid Indentation (Brinell Type) Hardness Test Method".

[0097] Table 3

[0098]

[0099]

[0100] It can be seen from Table 3 that the polytetrafluoroethylene soft belt bushing prepared in the embodiment of the present invention has excellent corrosion resistance and wear resistance, and has good mechanical properties, which is far superior to the bushing made of pure PTFE.

[0101] It can be seen from Examples 2 to 4 that when the amount of hydrophobic SiO2 increases, its friction coefficient decreases.

[0102] It can be seen from Examples 2, 5 and 6 that when only the content of aluminum silicate, carbon fiber and the like is reduced, the indentation hardness is reduced and the friction coefficient does not change significantly.

[0103] However, the components of the modified PTFE materials of Comparative Examples 1 to 7 are omitted, which results in weakening of at least one of the properties of corrosion resistance, wear resistance and mechanics.

[0104] From the comparison between comparative example 1 and example 2, it can be seen that when the hydrophobic SiO2 is deleted, the friction coefficient increases significantly and the indentation hardness decreases slightly, that is, the mechanical properties decrease slightly and the anti-corrosion performance decreases.

[0105] By comparing Comparative Example 2 and Comparative Example 5 with Example 2, it can be seen that when aluminum silicate is deleted, the friction coefficient is slightly reduced, the indentation hardness is significantly reduced, and it can be seen that the mechanical properties are significantly deteriorated, the friction resistance is not reduced, and the anti-corrosion performance does not change significantly; when carbon fiber is deleted, the indentation hardness is significantly reduced, and it can be seen that the mechanical properties are significantly deteriorated; the friction resistance is slightly reduced, and the anti-corrosion performance does not change significantly.

[0106] By comparing Comparative Examples 3 to 4 and Comparative Examples 6 to 7 with Example 2, it can be seen that when PDMS-OH is deleted, the friction coefficient and indentation hardness do not change significantly, but the anti-corrosion performance is weakened due to the decreased bonding between the bushing and the lining; the deletion of polyethylene, tert-butyl vinyl carbonate and methyltriacetoxysilane reduces the anti-corrosion performance and wear resistance.

[0107] Example 7

[0108] The effects of different zinc-nickel composite powders on bushing performance are studied. A method for preparing a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing, the steps are as follows:

[0109] S1. Select 304 stainless steel mesh as the substrate, and use a high-pressure cold spraying method (pressure of 6 MPa, temperature of 600°C, working gas of nitrogen) to spray the zinc-nickel composite powder of group E-22 prepared in Example 1 on the surface of the stainless steel mesh to form a zinc-nickel composite coating; then keep the stainless steel mesh at 1080°C for 1.5h, and then cool it at a rate of 50°C / h to 500°C, and then air-cool it to room temperature.

[0110] S2. The annealed stainless steel mesh is paved with PTFE material (the modified PTFE material of group E-11 obtained in Example 1), including paving, drying, primary rolling, plasticizing, fine rolling, and hemp rolling to prepare a corrosion-resistant and wear-resistant plate. The obtained plate is then placed on an automated soft belt production line to obtain a stainless steel-based polytetrafluoroethylene soft belt bushing.

[0111] S23. Soak the soft belt bushing in a degreasing agent for 4 minutes, then take it out and rinse it with running water, put it in a 70°C passivation solution for 30 minutes, then wash off the passivation solution on the surface of the workpiece with running water, put it in a 70°C consolidation solution for 20 minutes, then wash off the consolidation solution on the surface of the workpiece with running water, put it in a sealing solution for 4 minutes, finally take out the workpiece and dry it.

[0112] Example 8

[0113] The difference between this embodiment and embodiment 2 is that the zinc-nickel composite powder adopts the zinc-nickel composite powder of group E-23 prepared in embodiment 1, and the other preparation steps are the same as those in embodiment 2.

[0114] Example 9

[0115] The difference between this embodiment and embodiment 2 is that the zinc-nickel composite powder adopts the zinc-nickel composite powder of group E-24 prepared in embodiment 1, and the other preparation steps are the same as those in embodiment 2.

[0116] Example 10

[0117] The difference between this embodiment and embodiment 2 is that the zinc-nickel composite powder adopts the zinc-nickel composite powder of group E-25 prepared in embodiment 1, and the other preparation steps are the same as those in embodiment 2.

[0118] Embodiment 11

[0119] The difference between this embodiment and embodiment 2 is that the zinc-nickel composite powder adopts the zinc-nickel composite powder of group E-26 prepared in embodiment 1, and the other preparation steps are the same as those in embodiment 2.

[0120] Comparative Example 8

[0121] The difference between this comparative example and Example 2 is that the zinc-nickel composite powder adopts the zinc-nickel composite powder of group C-21 prepared in Example 1, and the other preparation steps are the same as those in Example 2.

[0122] Comparative Example 9

[0123] The difference between this comparative example and Example 2 is that the zinc-nickel composite powder adopts the zinc-nickel composite powder of group C-22 prepared in Example 1, and the other preparation steps are the same as those in Example 2.

[0124] Comparative Example 10

[0125] The difference between this comparative example and Example 2 is that the zinc-nickel composite powder adopts the zinc-nickel composite powder of group C-23 prepared in Example 1, and the other preparation steps are the same as those in Example 2.

[0126] Comparative Example 11

[0127] The difference between this comparative example and Example 2 is that the zinc-nickel composite powder adopts the zinc-nickel composite powder of group C-24 prepared in Example 1, and the other preparation steps are the same as those in Example 2.

[0128] The zinc-nickel composite powders and usage conditions of each embodiment are shown in Table 4 below. The bushings prepared in Examples 7 to 11 and Comparative Examples 8 to 11 are used as samples to test their friction performance, corrosion resistance and hardness, which are the same as in Example 2.

[0129] Table 4

[0130] Test subjects Zinc-nickel composite powder Friction coefficient Neutral salt spray test CASS test Brinell hardness / HB Example 2 E-21 0.012 conform to conform to 297.1 Example 7 E-22 0.013 conform to conform to 304.5 Example 8 E-23 0.015 conform to conform to 307.1 Example 9 E-24 0.017 conform to conform to 312.9 Example 10 E-25 0.013 conform to conform to 318.3 Embodiment 11 E-26 0.013 conform to conform to 300.8 Comparative Example 8 C-21 0.017 conform to Not Compliant 201.4 Comparative Example 9 C-22 0.015 conform to Not Compliant 241.12 Comparative Example 10 C-23 0.014 conform to Not Compliant 255.6 Comparative Example 11 C-24 0.013 conform to Not Compliant 262.9 Control group / 0.018 Not Compliant Not Compliant 187.7

[0131] It can be seen from Table 4 that the polytetrafluoroethylene soft belt bushing prepared in the embodiment of the present invention has excellent corrosion resistance and wear resistance, and has good mechanical properties, which is far superior to the bushing made of zinc-nickel-free coating.

[0132] However, the composition and preparation steps of the zinc-nickel composite powders of Comparative Example 8 to Comparative Example 11 are adjusted, which results in weakening of at least one property of corrosion resistance, wear resistance and mechanics.

[0133] From the comparison of Example 2 and Example 7 to Example 9, it can be seen that when the amount of Zn-ZuO nanoalloy increases and the amount of nickel powder decreases, the indentation hardness and friction coefficient both increase, indicating that the mechanical properties are optimized but the wear resistance is reduced, and the anti-corrosion performance is reduced.

[0134] From the comparison between Example 7 and Example 10 to Example 11, it can be seen that as the oxygen flow rate increases, the indentation hardness first increases and then decreases, the friction coefficient remains unchanged, and the anti-corrosion performance decreases.

[0135] By comparing Comparative Examples 8 and 9 with Example 2, it can be seen that when Zn-ZuO nanoalloy and nickel powder are used alone, the indentation hardness decreases significantly, that is, the mechanical properties decrease significantly; the friction coefficient increases slightly, that is, the wear resistance decreases slightly, and the anti-corrosion performance decreases.

[0136] By comparing Comparative Examples 10 and 11 with Example 7, it can be seen that when the oxygen flow rate is too small or too large, the indentation hardness is significantly reduced; the friction coefficient does not change significantly, and the anti-corrosion performance is reduced.

[0137] Example 12

[0138] The difference between this embodiment and embodiment 2 is that the annealing temperature is adjusted to 1050° C., and the other preparation steps are the same as those in embodiment 2.

[0139] Embodiment 13

[0140] The difference between this embodiment and embodiment 2 is that the annealing temperature is adjusted to 1100° C., and the other preparation steps are the same as those in embodiment 2.

[0141] Embodiment 14

[0142] The difference between this embodiment and embodiment 2 is that the annealing time is adjusted to 1 hour, and the other preparation steps are the same as those in embodiment 2.

[0143] Embodiment 15

[0144] The difference between this embodiment and embodiment 2 is that the annealing time is adjusted to 2 hours, and the other preparation steps are the same as those in embodiment 2.

[0145] Comparative Example 12

[0146] The difference between this comparative example and Example 2 is that no annealing treatment is performed, and the other preparation steps are the same as those in Example 2.

[0147] Comparative Example 13

[0148] The difference between this comparative example and Example 2 is that no passivation treatment is performed, and the other preparation steps are the same as those of Example 2.

[0149] The bushings prepared in Examples 12 to 15 and Comparative Examples 12 and 13 were used as samples to test their friction performance, corrosion resistance and hardness. The results are shown in Table 5.

[0150] Table 5

[0151]

[0152]

[0153] It can be seen from Table 5 that annealing and passivation treatment improve the corrosion resistance and wear resistance and mechanical properties of the PTFE soft belt bushing. Any deletion of any step will affect the performance of the PTFE soft belt bushing.

[0154] From the comparison between Example 2 and Example 12 to Example 13, it can be seen that with the increase of annealing temperature, the indentation hardness increases; the friction coefficient first decreases and then increases, but the amplitude is not large.

[0155] From the comparison between Example 2 and Example 14 to Example 15, it can be seen that as the annealing time increases, the indentation hardness increases, and the friction coefficient does not change significantly.

[0156] By comparing Comparative Example 12 with Example 2, it can be seen that after deleting the annealing treatment, the indentation hardness is greatly reduced, that is, the mechanical properties are greatly reduced; the friction coefficient increases slightly, that is, the wear resistance is slightly reduced, and the anti-corrosion performance is reduced.

[0157] By comparing Comparative Example 13 with Example 2, it can be seen that after removing the passivation treatment, the indentation hardness is almost unchanged; the friction coefficient changes greatly, and the anti-corrosion performance decreases significantly.

[0158] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing, characterized in that: The preparation method comprises the following steps: The stainless steel mesh with zinc-nickel composite powder cold-sprayed on the surface is annealed to serve as a substrate; The modified PTFE material is laid on the mesh and surface of the stainless steel mesh through a plasticizing process, and the stainless steel mesh is covered therein to make it serve as a skeleton, thereby obtaining a polytetrafluoroethylene soft belt wear-resistant material with a mutually covering structure; The soft belt bushing is made of the polytetrafluoroethylene soft belt material through an automated molding process of loading, feeding, unloading, arranging, curling, turning, flanging and shaping; The soft belt bushing after cleaning and impurity removal is immersed in passivation liquid, consolidation liquid and sealing liquid in turn for passivation treatment, and after drying, the anti-corrosion and wear-resistant PTFE soft belt bushing is obtained; The annealing treatment is specifically: maintaining the temperature at 1050°C-1100°C for 1h-2h, then cooling to 500°C at a rate not exceeding 50°C / h, and then air cooling or furnace cooling.

2. The method for preparing a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing according to claim 1, characterized in that: The passivation treatment is specifically as follows: Clean and remove impurities from the surface of the soft belt bushing, place it in a passivation solution at 70±5℃ for 20 to 40 minutes, and remove the residual passivation solution after cleaning; Place in a 60-70°C consolidation solution for 15-20 minutes, and remove the remaining consolidation solution after washing; Place in blocking solution for 3-5 minutes and dry.

3. The method for preparing a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing according to claim 1, characterized in that: Before annealing, the zinc-nickel composite powder is sprayed on the surface of the stainless steel mesh by a high-pressure cold spraying method.

4. The method for preparing a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing according to claim 1, characterized in that: The modified PTFE material comprises the following components in weight percentage: 5% to 15% hydrophobic SiO2, 5% to 10% aluminum silicate powder, 1% to 5% hydroxyl-terminated PDMS, 1% to 3% polyethylene, 1% to 3% carbon fiber, 1% to 3% versatate vinyl carbonate, and 0.5% to 1% methyltriacetoxysilane; the balance is polytetrafluoroethylene powder.

5. The method for preparing a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing according to claim 4, characterized in that: The hydroxyl-terminated PDMS has a hydroxyl functional group at the end of the PDMS molecular chain, and is monohydroxyl-terminated or dihydroxyl-terminated.

6. The method for preparing a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing according to claim 3, characterized in that: The preparation method of the zinc-nickel composite powder comprises: The zinc alloy powder is ball-milled into nano-scale powder, and then heat-treated at 600°C to 700°C for 3h to 5h under oxygen flow to obtain Zn-ZuO nano-alloy; The Zn-ZuO nano alloy and nickel powder are mixed in proportion and ball-milled to obtain the zinc-nickel composite powder; The weight percentage of the Zn-ZuO nano alloy and the nickel powder is: 40% to 70% of the Zn-ZuO nano alloy and 30% to 60% of the nickel powder.

7. The method for preparing a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing according to claim 6, characterized in that: The oxygen flow rate is 50% to 70% of the theoretical amount.

8. The method for preparing a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing according to claim 3, characterized in that: In the high-pressure cold spraying method, the pressure is 5MPa-10MPa, the temperature is 500-900°C, and the working gas is nitrogen and / or argon.

9. The method for preparing a corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing according to claim 4, characterized in that: The method for preparing the hydrophobic SiO2 is as follows: ethyl orthosilicate and tetrahydrofuran are mixed in a molar ratio of 1:5 to 6, deionized water is added, concentrated sulfuric acid is added dropwise to a pH of 3 to 4, the reaction is performed at room temperature for 8 to 16 hours, 3-(methacryloyloxy)propyltrimethoxysilane is added and stirred evenly, the solid-liquid separation is performed after standing, and the hydrophobic SiO2 is obtained after drying.

10. A corrosion-resistant and wear-resistant polytetrafluoroethylene soft belt bushing obtained by the preparation method according to any one of claims 1 to 9.